Evolutionary features of a prolific subtype of avian influenza A virus in European waterfowl. Issue 2 (27th August 2022) - Wille, Michelle; Tolf, Conny; Latorre-Margalef, Neus; Fouchier, Ron A M; Halpin, Rebecca A; Wentworth, David E; Ragwani, Jayna; Pybus, Oliver G; Olsen, Björn; Waldenström, Jonas
Abstract: Avian influenza A virus (AIV) is ubiquitous in waterfowl and is detected annually at high prevalence in waterfowl during the Northern Hemisphere autumn. Some AIV subtypes are globally common in waterfowl, such as H3N8, H4N6, and H6N2, and are detected in the same populations at a high frequency, annually. In order to investigate genetic features associated to the long-term maintenance of common subtypes in migratory ducks, we sequenced 248 H4 viruses isolated across 8 years (2002–9) from mallards ( Anas platyrhynchos ) sampled in southeast Sweden. Phylogenetic analyses showed that both H4 and N6 sequences fell into three distinct lineages, structured by year of isolation. Specifically, across the 8 years of the study, we observed lineage replacement, whereby a different HA lineage circulated in the population each year. Analysis of deduced amino acid sequences of the HA lineages illustrated key differences in regions of the globular head of hemagglutinin that overlap with established antigenic sites in homologous hemagglutinin H3, suggesting the possibility of antigenic differences among these HA lineages. Beyond HA, lineage replacement was common to all segments, such that novel genome constellations were detected across years. A dominant genome constellation would rapidly amplify in the duck population, followed by unlinking of gene segments as a result of reassortment within 2–3 weeks following introduction. These data help reveal the evolutionary dynamics exhibited by AIV on both annual and decadal scales in an important reservoir host.